Differentiation Strategy and Performance of Media Houses in Kenya - Chief, Lyn Kwamboka; Mukulu, Elegwa; Karanja, Kabare (European Journal of Business and Strategic Management, 2025)
Purpose: The aim of the study was to determine the relationship between differentiation strategy and the performance of the media houses in Kenya. The study objectives were to determine the effect of differentiation strategy and the performance of the media houses and to establish the moderating role of technology on the relationship between differentiation strategy and performance of the media houses in Kenya. Methodology: The study adopted survey research design. The target population was the 41 media houses in Kenya. The study targeted the top management of the media houses which comprised of the Finance, Marketing, Operations and information Communication Departments. According to the human resource of the organizations, there are about 1,976 management staff in the media houses in Kenya. 204 respondents were sampled purposive, stratified and simple random sampling. Data was collected using structured questionnaires and interview guides. Data was analysed using both descriptive and inferential statistics which included regression and moderation analysis. The researcher also tested the hypothesis. The results were presented in tables. Findings: The study established that customers generally perceive the products/services of the media firms as unique. Differentiation strategy was applied first on products followed by market and price. The media firms used digital formats to record news and programmes. Further, most of the media firms were run on digital systems while also ensuring that the presentation of programmes were different from those of their competitors. Differentiation was also by way of development of unique superior products than competitors. The study found a positive and significant effect of product differentiation strategy on the firm performance. This led to the rejection of the null hypothesis and acceptance of the alternative that product differentiation had a positive significant effect on the performance of media firms in Kenya. The incorporation of technology adoption as a moderator had a slight effect on the effect of differentiation on firm performance. The study established that moderating effect of technology of differentiation had a positive significant effect of the media firm performance. Unique Contribution to Theory, Practice and Policy: The study recommends that the management of media firms should embrace more differentiation strategy as it has proven in the current study. The firms should focus on making unique products to be competitive and enhance the performance. The study further recommends that media firm should embrace the best technology as the current study has demonstrated that technology has a significant moderating effect on the differentiation strategy and media firm performance.